Mitotic counts in breast cancer should be standardized with a uniform sample area. Issue 1 (December 2017) - Bonert, Michael; Tate, Angela
Abstract Background Mitotic rate is routinely assessed in breast cancer cases and based on the assessment of 10 high power fields (HPF), a non-standard sample area, as per the College of American Pathologists cancer checklist. The effect of sample area variation has not been assessed. Methods A computer model making use of the binomial distribution was developed to calculate the misclassification rate in 1, 000, 000 simulated breast specimens using the extremes of field diameter (FD) and mitotic density cutoffs (3 and 8 mitoses/mm2 ), and for a sample area of 5 mm2 . Mitotic counts were assumed to be a random sampling problem using a mitotic rate distribution derived from an experimental study (range 0–16.4 mitoses/mm2 ). The cellular density was 2500 cell/mm2 . Results For the smallest microscopes (FD = 0.40 mm, area 1.26 mm2 ) 16% of cases were misclassified, compared to 9% of the largest (FD 0.69 mm, area 3.74 mm2 ), versus 8% for 5 mm2 . An excess of 27% of score 2 cases were misclassified as 1 or 3 for the lower FD. Conclusion Mitotic scores based on ten HPFs of a small field area microscope are less reliable measures of the mitotic density than in a bigger field area microscope; therefore, the sample area should be standardized. When mitotic counts are close to the cut-offs the score is less reproducible. These cases could benefit from using larger sample areas. A measure of mitotic density variation due to sampling may assist in the interpretation of the mitotic score.